Numerical optimisation on the retrofitting of oxy-coal combustion in cement rotary kiln - Guanshuo HUANG; Yuegui ZHOU (Meitan xuebao)
Cement production is a high carbon dioxide emission process, where carbon emissions from coal combustion constitute a significant part of the carbon emissions from cement rotary kilns. The advantages of oxy-fuel combustion technology in carbon capture and utilization in power station boilers have gained a widespread attention for its application in industrial furnaces. Previous researchers have investigated the concentration of components inside the kiln and the combustion characteristics after the retrofit of oxy-fuel combustion in cement rotary kilns. However, the method of matching the heat transfer characteristics after the retrofit of oxy-fuel combustion in the cement rotary kilns with the original air atmosphere has not been well studied. In order to obtain the optimal strategy for the retrofitting cement rotary kilns with oxy-fuel combustion while ensuring cement production quality, a three-dimensional modeling of oxy-coal combustion in a 500 kW cement rotary kiln combustion test furnace was carried out using the CFD software. The effects of total oxygen concentration (25%-35%), the oxygen distribution methods of primary and secondary streams under constant total oxygen concentration, and secondary stream preheating temperature (650-950 ℃) on heat transfer characteristics and flame length in the furnace were studied. The simulation results showed that under the oxy-fuel combustion atmosphere, the flame length at different total oxygen concentrations increased by 5%-8% compared to the air atmosphere. The peak temperature and heat flux in the furnace significantly increased with the increase of total oxygen concentration, and the total heat flux and peak temperature in the furnace were the same as those in the air atmosphere when the total oxygen concentration was 29% and 35% respectively. Keeping the total oxygen concentration at 29%, changing the oxygen distribution method of primary and secondary streams, the change range of the difference between the total heat flux and the heat flux under the air atmosphere was within 3% as the oxygen concentration of primary stream increased from 0 to 80%. And with the oxygen concentration of primary stream at 60%, while ensuring that the total heat flux was basically the same as that under the air atmosphere, the difference in the along-furnace heat flux from the air atmosphere could be further reduced. At a total oxygen concentration of 29% and a primary stream oxygen concentration of 60%, when the secondary stream temperature increased from 650 ℃ to 950 ℃, the total heat flux and flame length increased by 16% and 4% respectively, and when the secondary stream temperature was 720-760 ℃, it could achieve the same total heat flux match in the kiln as the air atmosphere.